The effect of COVID-19 pandemic and wearing face masks on ophthalmology practice: What is known so far? A narrative review - Abu-Ismail, Luai; Al-Shami, Khayry; Al-Shami, Manar; Nashwan, Abdulqadir J. (Frontiers in Medicine, 2022)
Facemasks, along with other preventive measures, can help slow the spread of COVID-19. Despite the positive effect of the mask in combating the virus, it has some negative effects on the human body that must be followed up on and reduced. This paper discusses the impact of wearing facemasks on the eye and the common issues associated with using them. The search was conducted through a literature search of electronic databases like PubMed and Google Scholar. Only articles published in English were included. A total of 39 relevant articles were deemed eligible. The titles and abstracts of 20 papers were screened after the duplicate articles were removed and underwent full-text screening. The review comprised both prospective and retrospective investigations, case reports, and series reporting ocular symptoms following the use of facemasks. The COVID-19 pandemic affected ophthalmology practices in managing patients. New factors must be considered, especially when dealing with Anti-VEGF injections and the risk of endophthalmitis, glaucoma patients' tests and symptoms, and the emerging symptoms associated with the COVID-19 vaccination. The use of facemasks and breathing aids seemed to influence the tear film.